2020
DOI: 10.1007/s11033-020-05427-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: β adrenergic receptor modulated signaling in glioma models: promoting β adrenergic receptor-β arrestin scaffold-mediated activation of extracellular-regulated kinase 1/2 may prove to be a panacea in the treatment of intracranial and spinal malignancy and extra-neuraxial carcinoma

Abstract: Neoplastically transformed astrocytes express functionally active cell surface β adrenergic receptors (βARs). Treatment of glioma models in vitro and in vivo with β adrenergic agonists variably amplifies or attenuates cellular proliferation. In the majority of in vivo models, β adrenergic agonists generally reduce cellular proliferation. However, treatment with β adrenergic agonists consistently reduces tumor cell invasive potential, angiogenesis, and metastasis. β adrenergic agonists induced decreases of inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 145 publications
(324 reference statements)
0
2
0
Order By: Relevance
“…Erk1/2 signaling pathway, as the most important pathway in the MAPK signaling pathway, was closely related to cell proliferation, migration, apoptosis, skeleton formation, and maintenance (Koga et al., 2019), and had been considered as an important target for the treatment of malignant tumors (Ghali & Ghali, 2020) for its close relationship with angiogenesis (Medfai et al., 2019; Zhang et al., 2019). Exosomal miRNAs regulating angiogenesis was also closely associated with the Erk1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erk1/2 signaling pathway, as the most important pathway in the MAPK signaling pathway, was closely related to cell proliferation, migration, apoptosis, skeleton formation, and maintenance (Koga et al., 2019), and had been considered as an important target for the treatment of malignant tumors (Ghali & Ghali, 2020) for its close relationship with angiogenesis (Medfai et al., 2019; Zhang et al., 2019). Exosomal miRNAs regulating angiogenesis was also closely associated with the Erk1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated the exosome-dependent manner of MOBs transporting let-7f-5p into ECs and confirmed the positive regulatory effects of MOB-Exo let-7f-5p on the angiogenic capabilities of ECs. et al, 2019), and had been considered as an important target for the treatment of malignant tumors (Ghali & Ghali, 2020) for its close relationship with angiogenesis (Medfai et al, 2019;Zhang et al, 2019). Exosomal miRNAs regulating angiogenesis was also closely associated with the Erk1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%